Characterization of drug-resistant neuroblastoma cell lines by comparative genomic hybridization - Bedrnicek, J; Vicha, A; Jarosova, M; Holzerova, M; Cinatl, J; Michaelis, M; Cinatl, J; Eckschlager, T (Neoplasma, 2005)
Three parental neuroblastoma cell lines and nine derived lines resistant to Vincristin, Doxorubicin and Cisplatin, respectively, using CGH were studied. CGH profiles of all three parental cell lines were obtained using DNA from a healthy volunteer as reference DNA. Labeled DNA from each of the drug resistant daughter cell lines and labeled DNA from their parental sensitive cell lines were hybridized to obtain a comparison of gains and losses that accompanied the development of resistance for that particular drug. All three parental cell lines were characterized by typical findings for high risk neuroblastoma: N-myc amplification, gain of 17q, and loss of 1p36.2-36.3. Acquired drug resistance in the neuroblastoma cell lines appeared to be accompanied by a large array of DNA sequence copy number changes. The regions frequently affected in chemo-resistant cell lines included gains of 13q14.1-32, and 7q11.2-31.3, 4 q. Amplifications were seen at 7q 21.1 consistent with MDR1 amplification in UKF-NB-2 VCR, UKF-NB-3 DOXO, UKF-NB-4 VCR, and UKF-NB-4 DOXO, but not in any Cisplatin resistant line. All Cisplatin and Doxorubicin and two Vincristin resistant line (UKF-NB-2 VCR and UKF-NB-4 VCR) had a deletion of part of 19q or the whole 19 chromosome. All lines resistant to Vincristin or Doxorubicin and two Cisplatin resistant lines (UKF-NB-2 CDDP and UKF-NB-4 CDDP) had a deletion of at least part of 17q, UKF-NB-4 DOXO had deletion of the whole chromosome 17. The loss of 17q may cause chemoresistance by deletion of topoisomerase IIalpha gene. Deletion of 19 q in all but one chemo-resistant lines may influence of cytochromes P450 genes which are located on 19q13.2. Also gains of 15q 22, which were detected in UKF-NB-4 VCR, UKF-NB-2 DOXO and UKF-NB-4 DO X O, may affect other cytochromes P450 genes.
Keywords: Gene Dosage; doxorubicin; protinádorové látky; Cell Line, Tumor; genová dávka; DNA nádorová; chemorezistence; Image Processing, Computer-Assisted; Vincristine; Neuroblastoma; DNA, Neoplasm; počítačové zpracování obrazu; lidé; Humans; vinkristin; cisplatina; Drug Resistance, Neoplasm; nádorové buněčné linie; Cisplatin; neuroblastom; Doxorubicin; Antineoplastic Agents